Genital ulcer as a new clinical clue to PFAPA syndrome. (1st April 2015) - Scattoni, R.; Verrotti, A.; Rinaldi, V.E.; Paglino, A.; Carelli, A.; D'Alonzo, R.
Summary: Vaginal ulcers can be associated with a number of different diseases. We describe two girls who presented genital ulcers as a persistent symptom of PFAPA (periodic fever, aphthous stomatitis, pharyngitis, cervical adenitis) syndrome. The possibility of considering this clinical manifestation as a clue for the diagnosis of PFAPA is discussed.